Ultrathin one-dimensional molybdenum telluride quantum wires synthesized by chemical vapor deposition - Yoo, Youngdong; Jeong, Jong Seok; Ma, Rui; Koester, Steven J.; Johns, James E. (Chemistry of Materials, 2020)
One-dimensional (1D) transition-metal chalcogenides (TMCs) are attracting increasing scientific and technological interest, especially for ultrasmall electronic interconnects and highly active catalysts. However, it is quite challenging to synthesize high-quality 1D TMCs over large areas on substrates. Here, we report on an atmospheric-pressure vapor-phase synthetic strategy for growing ultrathin 1D Mo6Te6 wires on various substrates such as Si3N4, SiO2, and doped SiC, employing double MoO3 sources. Scanning transmission electron microscopy confirms that the ultrathin 1D Mo6Te6 wires possessing thicknesses of 3−5 nm grow laterally to form wire networks. Lattice-resolution electron energy loss spectroscopy mapping clearly shows intensity variations of Mo-M4,5 and Te-M4,5 signals originating from Mo and Te atoms in the monoclinic Mo6Te6 structure. Furthermore, we investigate the vibrational modes of 1D Mo6Te6 wire networks, confirming that the two characteristic Raman peaks at 155 and 245 cm−1 are associated with resonance Raman scattering. The 1D Mo6Te6 wire networks not only possess excellent transparency in the near-infrared range but also are electrically conductive. They also exhibit temperature-dependent Hall effects. We believe that these ultrathin 1D Mo6Te6 wires are auspicious materials for future electronics and catalysis.
Keywords: Electrically conductive; Electronic interconnects; Intensity variations; Resonance Raman scattering; Scanning transmission electron microscopy; Synthetic strategies; Temperature dependent; Transition metal chalcogenides